Analytical method for calculating losses in overhead lines of electric power systems taking into account changes in load and weather conditions - E. V. Petrova (Омский научный вестник)
In this article, the subject of research is methods for calculating active power losses in electric power overhead lines, taking into account the temperature dependence of active resistances. An analytical approach based on the Ferrari method for calculating the wire temperature and active power losses under conditions of forced convection is proposed and substantiated in detail. The peculiarity of the approach is universality, which is expressed in the fact that the developed mathematical model allows us to consider non-insulated and insulated wires on power transmission lines from a single position. The results of calculating the temperature and active power losses by the proposed method, the least squares method and the iterative method are presented. The high accuracy of the coincidence of the results obtained by various methods is noted.